Beyond PD‐L1—Identification of Further Potential Therapeutic Targets in Oral Cancer - Weber, Manuel; Lutz, Rainer; Olmos, Manuel; Glajzer, Jacek; Baran, Christoph; Nobis, Christopher-Philipp; Möst, Tobias; Eckstein, Markus; Kesting, Marco Rainer; Ries, Jutta (Cancers, 2022)
Background: The involvement of immune cell infiltration and immune regulation in the progression of oral squamous cell carcinoma (OSCC) is shown. Anti‐PD‐1 therapy is approved for the treatment of advanced OSCC cases, but not all patients respond to immune checkpoint inhibi-tors. Hence, further targets for therapeutic approaches are needed. The number of identified cellular receptors with immune checkpoint function is constantly increasing. This study aimed to perform a comparative analysis of a large number of immune checkpoints in OSCC in order to identify possible targets for therapeutic application. Materials and Methods: A NanoString mRNA analysis was performed to assess the expression levels of 21 immune regulatory checkpoint molecules in OSCC tissue (n = 98) and healthy oral mucosa (NOM; n = 41). The expression rates were compared between the two groups, and their association with prognostic parameters was determined. Additionally, relevant correlations between the expression levels of different checkpoints were examined. Results: In OSCC tissue, significantly increased expression of CD115, CD163, CD68, CD86, CD96, GITRL, CD28 and PD‐L1 was detected. Additionally, a marginally significant increase in CD8 expression was observed. BTLA and PD‐1 levels were substantially increased, but the differential expression was not statistically significant. The expression of CD137L was significantly downregulated in OSCC compared to NOM. Correlations between immune checkpoint expression levels were demonstrated, and some occurred specifically in OSCC tissue. Conclusions: The upregulation of inhibitory receptors and ligands and the downregulation of activators could contribute to reduced effector T‐cell function and could induce local immunosuppression in OSCC. Increased expression of activating actors of the immune system could be explained by the increased infiltration of mye-loid cells and T‐cells in OSCC tissue. The analysis contributes to the understanding of immune es-cape in OSCC and reveals potential targets for oral cancer immunotherapy.
CRIS-Team Scopus Importer:2022-04-15
Keywords: head and neck cancer; HNSCC; immune checkpoints; immunotherapy; macro-phage; MDSC; OSCC; T‐cell

Consistent Value of Two-Stage Pedicle Flaps in the Age of Microsurgical Maxillofacial Reconstruction - Frohwitter, Gesche; Lutz, Rainer; Baran, Christoph; Weber, Margarete; Nobis, Christopher-Philipp; Rau, A.; Kesting, Marco Rainer (Journal of Maxillofacial and Oral Surgery, 2021)
Introduction: Up to the second half of the twentieth century, pedicled flaps marked the gold standard in reconstructive surgery. Followed by the introduction of microsurgical techniques, these flaps were increasingly abandoned. We conducted a retrospective study to determine the value of two-stage pedicle flaps in modern maxillofacial reconstruction. Material & Methods: A chart review from October 2017 to November 2020 was performed to identify patients who were treated by a two-stage pedicle flap in our Department of Oral and Maxillofacial Surgery. Results: A total of 31 patients, 17 female and 14 males received 36 two-stage pedicle flaps. All patients were in noticeably impaired health condition with a majority of ASA-score 3. The defect location mainly contained extraoral resections (58.3%). A variety of flaps were harvested consisting of buccal flaps, Abbe flaps, forehead flaps, deltopectoral flaps, nasolabial flaps, and a tubed flap. Discussion: The study outlines two indications for the use of two-stage pedicle flaps. Firstly, as a back-up strategy in heavily pre-treated wound beds and secondly in an almost contrarily indication as a first-choice reconstructive option of the facial skin in esthetic demanding cases. Conclusion: The timesaving and straight forward surgical approach as well as their low postsurgical complications and strong long-time success rates secure the two-stage pedicle flap a justified niche role in times of microsurgical maxillofacial reconstruction.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Back-up procedures; Pedicle flaps; Reconstructive surgery; Transplant autonomy

Dysregulation of immune checkpoint molecules in oral cancer - Weber, Manuel; Lutz, Rainer; Glajzer, Jacek; Werry, Jan-Erik; Baran, Christoph; Frohwitter, Gesche; Eckstein, Markus; Kesting, Marco Rainer; Ries, Jutta (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Expression of the Immune Modulators of the PD-1: PD-L1 Axis in oral Leukoplakia - Ries, Jutta; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Danzer, Eva; Bolzel, Stella; Büttner-Herold, Maike; Kesting, Marco Rainer; Weber, Manuel (2020)
EVALuna2:216185

Importance of the PD-1/PD-L1 Axis for Malignant Transformation and Risk Assessment of Oral Leukoplakia - Ries, Jutta; Agaimy, Abbas; Wehrhan, Falk; Baran, Christoph; Bolze, Stella; Danzer, Eva; Frey, Silke; Jantsch, Jonathan; Möst, Tobias; Büttner-Herold, Maike; Wickenhauser, Claudia; Kesting, Marco Rainer; et al. (Biomedicines, 2021)
Background: The programmed cell death ligand 1/programmed cell death receptor 1 (PD-L1/PD-1) Immune Checkpoint is an important modulator of the immune response. Overexpression of the receptor and its ligands is involved in immunosuppression and the failure of an immune response against tumor cells. PD-1/PD-L1 overexpression in oral squamous cell carcinoma (OSCC) compared to healthy oral mucosa (NOM) has already been demonstrated. However, little is known about its expression in oral precancerous lesions like oral leukoplakia (OLP). The aim of the study was to investigate whether an increased expression of PD-1/PD-L1 already exists in OLP and whether it is associated with malignant transformation. Material and Methods: PD-1 and PD-L1 expression was immunohistologically analyzed separately in the epithelium (E) and the subepithelium (S) of OLP that had undergone malignant transformation within 5 years (T-OLP), in OLP without malignant transformation (N-OLP), in corresponding OSCC and in NOM. Additionally, RT-qPCR analysis for PD-L1 expression was done in the entire tissues. Additionally, the association between overexpression and malignant transformation, dysplasia and inflammation were examined. Results: Compared to N-OLP, there were increased levels of PD-1 protein in the epithelial and subepithelial layers of T-OLP (PE = 0.001; PS = 0.005). There was no significant difference in PD-L1 mRNA expression between T-OLP and N-OLP (p = 0.128), but the fold-change increase between these groups was significant (Relative Quantification (RQ) = 3.1). In contrast to N-OLP, the PD-L1 protein levels were significantly increased in the epithelial layers of T-OLP (p = 0.007), but not in its subepithelial layers (p = 0.25). Importantly, increased PD-L1 levels were significantly associated to malignant transformation within 5 years. Conclusion: Increased levels of PD-1 and PD-L1 are related to malignant transformation in OLP and may represent a promising prognostic indicator to determine the risk of malignant progression of OLP. Increased PD-L1 levels might establish an immunosuppressive microenvironment, which could favor immune escape and thereby contribute to malignant transformation. Hence, checkpoint inhibitors could counteract tumor development in OLP and may serve as efficient therapeutic strategy in patients with high-risk precancerous lesions.
CRIS-Team WoS Importer:2021-03-19

MAGE-A expression in oral and laryngeal leukoplakia predicts malignant transformation - Baran, Christoph; Agaimy, Abbas; Wehrhan, Falk; Weber, Manuel; Hille, Verena; Brunner, Kathrin; Wickenhauser, Claudia; Siebolts, Udo; Nkenke, Emeka; Kesting, Marco Rainer; Ries, Jutta (Modern Pathology, 2019)
Leukoplakia is a potential precursor of oral as well as laryngeal squamous cell carcinoma. Risk assessment of malignant transformation based on the grade of dysplasia of leukoplakia often does not lead to reliable results. However, oral squamous cell carcinoma, laryngeal squamous cell carcinoma, and leukoplakia express single or multiple members of the melanoma-associated antigens A (MAGE-A) family, while MAGE-A are absent in healthy mucosal tissue. The present study aimed at determining if there is an association between the expression of MAGE-A in leukoplakia and malignant transformation to oral or laryngeal squamous cell carcinoma. Paraffin-embedded tissues of 205 oral and laryngeal leukoplakia, 90 corresponding tumors, and 40 healthy oral mucosal samples were included in the study. The grade of dysplasia of the leukoplakia samples was determined histopathologically. The leukoplakia samples were divided into lesions that transformed to oral and laryngeal squamous cell carcinoma (n = 91) and lesions that did not (n = 114) during a 5 years follow-up. The expression of MAGE-A3/6 and MAGE-A4 was analyzed by real-time RT-PCR. The expression of MAGE-A 1–4, 6, and 12 was determined by immunohistochemistry. A total of 59.3% of the transforming leukoplakia expressed at least one of the examined antigens as opposed to an expression rate of 3.5% of all non-transforming leukoplakia. There was no MAGE-A expression in healthy oral mucosa. The risk of malignant transformation was statistically significantly associated with MAGE-A expression in immunohistochemistry (p < 0.001) and real-time RT-PCR (MAGE-A3/6, p = 0.001; MAGE-A4, p = 0.002) analyses. There was no significant association between MAGE-A expression and the grade of dysplasia (“low-grade”, D0/D1; “high-grade”, D2/D3) in immunohistochemistry (p = 0.412) and real-time RT-PCR (MAGE-A3/6, p = 0.667; MAGE-A4, p = 0.756). It seems that the analysis of the MAGE-A expression profile may support the identification of leukoplakia at risk for malignant transformation. Therefore, efforts should be made to establish this analysis as a routine procedure in addition to conventional histopathology.
CRIS-Team Scopus Importer:2019-08-06

Malignant transformation of oral leukoplakia is associated with macrophage polarization - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Öztürk, Hatice Kübra; Neubauer, Kristina; Wickenhauser, Claudia; Kesting, Marco Rainer; Ries, Jutta (Journal of Translational Medicine, 2020)
BACKGROUND: Most oral squamous cell carcinomas (OSCC) occur on the basis of oral leukoplakias (OLP). The histologic degree of dysplasia is insufficient for the prediction of OLP malignant transformation. Immunologic parameters are gaining importance for prognostic assessment and therapy of cancer. M2 polarized macrophages were shown to be associated with OSCC progression and inferior prognosis. The current study aims to answer the question if OLP with malignant transformation into OSCC within 5 years differ from OLP without transformation regarding macrophage infiltration and polarization. METHODS: 201 specimens (50 transforming OLP, 53 non-transforming OLP, 49 corresponding OSCC and 49 healthy oral mucosa controls) were processed for immunohistochemistry. Samples were stained for CD68, CD163 and CD11c expression, completely digitalized and computer-assisted cell counting was performed. Epithelial and subepithelial compartments were differentially assessed. Groups were statistically compared using the Mann-Whitney U-test. A cut-off point for the discrimination of transforming and non-transforming OLP was determined and the association between macrophage infiltration and malignant transformation was calculated using the Chi-square test (χ2 test). RESULTS: Macrophage infiltration and M2 polarization in OLP with malignant transformation within 5 years was significantly increased compared to OLP without malignant transformation (p < 0.05). OSCC samples showed the highest macrophage infiltration and strongest M2 polarization (p < 0.05). Additionally, transforming OLP revealed a significant shift of macrophage infiltration towards the epithelial compartment (p < 0.05). χ2 test revealed a significant association of increased macrophage infiltration with malignant transformation (p < 0.05). CONCLUSION: Immunological changes precede malignant transformation of OLP. Increased macrophage infiltration and M2 polarization was associated with the development of oral cancer in OLP. Macrophage infiltration could serve as predictive marker for malignant transformation.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Carcinogenesis; CD11c; CD163; CD68; M1; M2; Macrophage polarization; Oral cancer; Oral leukoplakia; Oral squamous cell carcinoma; OSCC

PD1 expression and correlation with its ligands in oral cancer specimens and peripheral blood - Wehrhan, Falk; Weber, Manuel; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Kesting, Marco Rainer; Ries, Jutta (Journal of Cranio-Maxillofacial Surgery, 2021)
Objectives: This study analyzed the expression of the PD1 receptor in tumor tissue and peripheral blood of oral squamous cell carcinoma (OSCC) patients, and correlated it with the PD1 ligands PD-L1 and PD-L2. The currently low response rates of checkpoint inhibitor treatment in OSCC could be increased by a better understanding of immune checkpoint biology. Despite evidence in the literature for upregulation of PD1 checkpoint ligands in OSCC tissue, there has been no correlation analysis of the PD1 receptor with its ligands in tissue specimens and peripheral blood of OSCC patients.
CRIS-Team WoS Importer:2021-03-05

PD-L1 expression in peripheral blood samples of patients with oral squamous cell carcinomas - Ries, Jutta; Weber, Manuel; Baran, Christoph; Agaimy, Abbas; Buettner-Herold, M.; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (2018)
EVALuna2:34230

PD-L1 expression in tumor tissue and peripheral blood of patients with oral squamous cell carcinoma - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Preidl, Raimund; Neukam, Friedrich Wilhelm; Ries, Jutta (Oncotarget, 2017)
Immune checkpoints like programmed cell death-1 (PD-1) and its ligand PD-L1 are involved in immune escape mechanisms of solid tumors including oral squamous cell carcinoma (OSCC). Inhibitors of the pathway are successfully used for treating especially advanced disease. However, the physiological relevance of PD-1/PD-L1-signaling in OSCC is insufficiently understood. The aim of the study was to analyze if PD-L1 expression in tumor tissue and peripheral blood samples of OSCC patients is associated with histomorphological tumor parameters and if PD-L1 expression in patients is different from controls.OSCC tumor specimens showed a significantly higher PD-L1 expression than oral mucosa controls (p < 0.001; upregulation more than 3-fold). Cross-tabulation revealed an association of increased expression of PD-L1 mRNA in tissue specimens with malignancy (p < 0.001).OSCC cases with higher tumor grade and cases with lymph node metastases (N+) were significantly (p < 0.05) associated with increased PD-L1 expression in peripheral blood. Cross-tabulation revealed an significant association with lymph node metastases (N+) (p <= 0.002).PD-L1 mRNA expression was analyzed in tumor specimens and corresponding samples of healthy oral mucosa and peripheral blood of 45 OSCC patients and 36 healthy control persons using RT-qPCR analysis. A Mann-Whitney U-test, a cut-off point analysis and a Chi-square test were carried out.PD-L1 expression in OSCC could contribute to the immunosuppressive local tumor microenvironment. Increased malignant behavior (higher tumor grade, positive nodal status) might be associated with PD-L1 mediated systemic immune tolerance. Thus, PD-L1 expression in peripheral blood might be an indicator of the existence of metastatic disease (N+) in OSCC.
EVALuna2:25563

Pedicled buccal flaps as a backup procedure for intraoral reconstruction - Frohwitter, Gesche; Kesting, Marco Rainer; Rau, Andrea; Weber, Manuel; Baran, Christoph; Nobis, Christopher-Philipp; Büntemeyer, Tjark-Ole; Preidl, Raimund; Lutz, Rainer (Oral and maxillofacial surgery, 2022)
Background: Intraoral soft tissue deficiency and impaired wound beds are common problems after cleft and tumour surgery or after dental trauma. Frequently, limited defects are overtreated with extensive microvascular reconstruction procedures, but pedicled flaps remain useful, as they are simple to harvest, and they provide a reliable outcome. The buccal flap, first described in the 1970s, has been used for palatine lengthening in cleft patients over decades. In the following, we present an expanded indication in cases of palatal fistula, complex vestibulum, exposed bone in orthognathic surgery, and osteoradionecrosis. Methods: We conducted a retrospective chart review and report on all buccal flaps harvested in our department within the last 3 years with a follow-up period of at least half a year after flap surgery. Patients of all age groups and treatment indications in which a buccal flap was used were implicated in the evaluation. Results: Sixteen buccal flaps were performed in 10 patients. The median age at the time of surgery was 42 years, reaching from 12 up to 66 years. Fourteen buccal flaps were used for upper jaw or palatal coverage; two buccal flaps were used in the mandible. In terms of complications (four flaps; 25%), there were two partial flap failures, one wound dehiscence and one wound dehiscence. There were no failures of the remaining mucosal flap islands after pedicle dissection. Conclusion: The buccal flap is a reliable and straightforward approach to challenging intraoral wound beds with soft tissue deficiency. We thoroughly discuss the additional indications for buccal flap surgery, describe the harvest technique, and provide strategies to prevent intra- and postoperative complications.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Backup procedures; Cleft surgery; Oral surgery; Pedicle flaps; Reconstructive surgery

Prognostic significance of PD-L2 expression in patients with oral squamous cell carcinoma-A comparison to the PD-L1 expression profile - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Kesting, Marco Rainer; Ries, Jutta (Cancer Medicine, 2019)
BACKGROUND: Despite the observed association of increased PD-L1 expression in peripheral blood of oral squamous cell carcinoma (OSCC) patients with histomorphologic parameters, the role of the PD1 ligands-PD-L1 and PD-L2-is insufficiently understood. Aim of the study was to investigate whether the alterations of PD-L1 and PD-L2 expression in blood are associated with survival and could serve as immune monitoring parameter. Moreover, it should be analyzed if PD-L2 is differentially expressed in tissue and blood samples of OSCC patients compared to healthy controls and if there is an association of PD-L2 expression with histomorphologic and prognostic tumor parameters. METHODS: PD-L2 mRNA expression was analyzed in tumors and healthy oral mucosa specimens and in corresponding peripheral blood samples of 48 OSCC patients and 26 healthy controls using RT-qPCR. A cutoff point (COP) was determined and a chi-square test (χ2 test) was carried out. Survival analysis of PD-L2 and previously reported PD-L1 expression data was performed using Kaplan-Meier analysis (Log-rank test). RESULTS: PD-L2 expression in tissue samples was significantly (P < 0.001) higher in OSCC patients compared to healthy controls. A significant association of PD-L2 expression above the COP (positive) with malignancy was ascertained (P < 0.001). A significant (P = 0.01) association of previously reported PD-L1 expression rates in peripheral blood with survival could be shown. CONCLUSION: Peripheral blood PD-L1 expression might be a prognostic marker for OSCC patients and a possible parameter to monitor immune dysfunction in malign diseases. In the peripheral blood, PD-L1 might be more relevant for immune tolerance than PD-L2. Local PD-L2 expression in tissue samples might be useful as a diagnostic parameter for malignancy and could contribute to the immunosuppressive local microenvironment in OSCC.
EVALuna2:35498

Significance of altered PD-L1 expression in tumor tissue of oral squamous cell carcinomas - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Buettner-Herold, M.; Preidl, Raimund; Neukam, Friedrich Wilhelm; Ries, Jutta (2018)
EVALuna2:34231

The altered expression levels of miR-186, miR-494 and miR-3651 in OSCC tissue vary from those of the whole blood of OSCC patients - Ries, Jutta; Baran, Christoph; Wehrhan, Falk; Weber, Manuel; Motel, Constantin; Kesting, Marco Rainer; Nkenke, Emeka (Cancer Biomarkers, 2018)
BACKGROUND: Altered expressions of miR-186, miR-494 and miR-3651 in whole blood of OSCC patients have already been demonstrated. However, nothing is known about their expression in tumor tissues. This study aimed at evaluating differences in miRNA expression in OSCC tissues compared to healthy oral mucosa and at checking if the altered expression is reflected in corresponding blood. METHODS: In 53 OSCC and 40 healthy mucosal tissues the expression of miR-186, -494 and -3651 was determined by RT-qPCR and expression levels were compared between the groups. The altered expression in tissues was compared with that determined for corresponding blood. MiR-3651 target genes were identified using TargetScan software. RESULTS: Differential expression of miR-186 and miR-494 could not be observed in tumor tissues compared to normal mucosa (pmiR-186= 0.13; pmiR-494= 0.35). Contrary to the detected upregulation of the miR-3651 in the blood of OSCC patients, a significant downregulation was observed in OSCC tissues. A significant correlation between underexpression and diagnosis was ascertained (p= 0.0001). 1710 possible target genes of miR-3651 were identified. CONCLUSIONS: Decreased expression of miR-3651 in OSCC tissues may be a diagnostic biomarker. The opposite change in expression level in the blood might indicate different functions of this miRNA in circulation and tissue.
EVALuna2:35500